2018
DOI: 10.5334/uproc.38
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue response evaluation of stainless steel SS 304 L(N) and SS 316 L(N) through cyclic ball indentation studies

Abstract: This paper presents the results of an experimental investigation of fatigue response of stainless steel SS 304 L(N) and SS 316 L(N) using cyclic ball indentation test method. A Tungsten Carbide (WC) spherical ball of 1.57 mm diameter is used for applying compression-compression fatigue cycling on the test specimen having a nominal thickness of 5 mm; the displacement response is monitored as a function of every cycle of loading. The study focused on cases where the stainless steel specimens were welded by two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…High starting frequency implies that the shock is propagating through a high density region and hence a low formation height. Some of the coronal shock waves propagate in the interplanetary space and become the source of type II radio radiation in the decametric to kilometric wave range (Gopalswamy et al 2005;Lu et al 2017;Prakash et al 2017). In some of the type II burst events, fundamental and/or harmonic bands are split into two morphologically similar lanes (Nelson & Melrose 1985).…”
Section: Introductionmentioning
confidence: 99%
“…High starting frequency implies that the shock is propagating through a high density region and hence a low formation height. Some of the coronal shock waves propagate in the interplanetary space and become the source of type II radio radiation in the decametric to kilometric wave range (Gopalswamy et al 2005;Lu et al 2017;Prakash et al 2017). In some of the type II burst events, fundamental and/or harmonic bands are split into two morphologically similar lanes (Nelson & Melrose 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis also revealed that both acreage and productivity increased favourably between the pre-and post WTO eras. Prakash (2018) highlighted the value of ginger growing and said that it is a significant cash crop in the North East. The North East's rural growers can make money from their ginger business.…”
Section: Introductionmentioning
confidence: 99%